Transdiagnostic mechanisms of mental health during the COVID-19 pandemic: associations of childhood trauma, maladaptive personality traits, emotion regulation, mentalizing, and pandemic-related distress - Holl, Julia; Berning, Anna; Kling, Laura; Taubner, Svenja; Georg, Anna; Volkert, Jana (Frontiers in psychology, 2024)
The outbreak of the COVID-19 pandemic has led to increased psychological distress. Transdiagnostic factors, including childhood trauma, maladaptive personality traits (MPTs), mentalizing, and emotion dysregulation are considered relevant to the development and maintenance of mental health problems. These factors probably play a significant role in individuals’ reactions to pandemic-related distress (PR distress). The aim of this study is to examine the associations with these transdiagnostic factors in relation to PR distress and psychopathological symptoms. Using a cross-sectional study design, we investigated a convenience sample of 6,451 adults (mean age=44.1; SD=11.8; 69.1% female, 30.3% male, 0.01% diverse) recruited via social media platforms in German-speaking countries (August 2020 - February 2021) by utilizing self-report instruments (PID5BF+, MentS, DERS-SF, PHQ-9, GAD-7, a composite PR distress score). Structural equation modeling was performed for data analysis. The results revealed significant associations between different types of childhood trauma and MPTs (-.14 < β < .48) as well as a parallel mediation of the relationship between MPTs and psychopathological symptoms via mentalizing (βanxiety=-.03; βdepression=.01) and emotion dysregulation (βanxiety=.24; βdepression=.23). Mentalizing and emotion dysregulation seem to play a significant role in relation between childhood trauma and MPTs and psychopathological symptoms during the COVID-19 pandemic. Thus, transdiagnostic factors may be a valuable target for the development of interventions aiming to reduce psychological distress related to a pandemic or other crises events. Specific prevention and intervention methods that target emotion dysregulation and mentalizing could help vulnerable individuals, particularly those with childhood trauma and MPTs, to protect against or alleviate the detrimental effects of PR distress on their mental health.